Enhancing Sea Turtle Conservation Efforts through Collaboration Approach: Case Study of ORI MA FALA Program, Ternate - TAUFIK, Muhammad; NAFILA, Fiki; ANGGARAINI, Sinki; RAMADANI, Aisyah Hadi; TAMAM, Muhammad Badrut (International Journal of Environmental, Sustainability, and Social Science, 2024)
Internationally turtles are listed on the IUCN red list and Appendix I of CITES (Convention on International Trade in Endangered Species), which means that their existence in nature is threatened. Ternate is well known for its endemic flora and fauna. On this small island, for example, various types of sea turtles have lived. Promotion of knowledge about sea turtle conservation is lacking. As a result, commercial exploitation of sea turtles is rampant in Tobololo. This study describes the role of the local community in maintaining the existence of sea turtles and how collaboration between stakeholders can improve sea turtle conservation efforts more effectively. Sea turtle conservation at Tobololo beach in ternate has used a multi-stakeholder collaborative approach by PT Pertamina Patra Niaga DPPU Babullah. Conservation is primarily carried out by the ORI MA FALA group. The success of the program in releasing hatchlings was 74.11% and the success in hatching was 87.4%.